The effect of prior exposure on the lightfastness of early synthetic dyes on textiles - Eric Hagan; Jennifer Poulin (Heritage Science, 2022)
Abstract Many studies have investigated light-induced damage to colourants in heritage collections using prepared samples of materials such as artist paints and dyed textiles. The body of research focuses primarily on the response of virgin materials, where colour change is assessed with respect to the original colour as light dose increases. From a practical perspective, most objects in museum collections have accumulated a significant light dose from illumination before acquisition, and subsequent years of exhibit lighting. When considering the risk of further degradation, it is often stated by heritage professionals that fugitive colourants with past light exposure are no longer as sensitive due to the slowing rate of visual damage. This is evident by studying ‘fading curves’, where the rate of colour change typically diminishes with increasing light dose. It remains unclear, however, to what degree the lightfastness of remaining colour changes with ongoing exposure. To address the issue, the light sensitivity of residual colour was investigated as a function of prior dose using a published dataset of colour measurements from textiles dyed with early synthetic colourants in the period of 1874–1905. The CIELAB colour values (D65/2°) for each material and dose increment were used to determine the future dose that causes a just-noticeable difference (JND), ΔE 00 = 1.7, starting at different amounts of past exposure. This involved resetting the reference CIELAB values to that of the residual colour after each prior dose. The analysis provides an extension of our earlier work, where only the initial lightfastness was reported. A summary of the findings illustrates the shifting distribution of lightfastness, toward higher Blue Wool (BW) ratings with increasing exposure. As the dose progresses, dyes that start at BW1 sensitivity progress to BW2, then BW3 and so on. The findings from this work may assist with boundary approximations of object sensitivity when prior light exposure is known, or a reasonable estimate is available. An analysis of experimental data is summarised as a tool for this type of decision-making process.